Strategic SWOT Analysis for Enhancing the Competitive Advantage of the Dental and Oral Hospital at Universitas Andalas - Rahmasari, Suci; Arini, Mustika; Ladyventini, Yona (Dentistry Faculty, 2025)
Background: The Dental and Oral Hospital of Andalas University (RSGM UNAND) in West Sumatra serves as both a healthcare provider and an academic institution. In a competitive healthcare environment, hospitals face challenges in maintaining and improving their service performance and visibility. Objective: This study aims to identify internal and external factors influencing the competitiveness of RSGM UNAND and to formulate appropriate strategic responses using SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis. Methods: This research employed a qualitative case study approach. Data collection involved in-depth interviews with key stakeholders, direct observation of hospital operations, and document analysis to obtain comprehensive insights into institutional strengths, weaknesses, and external dynamics. Results: The findings indicate that RSGM UNAND's main strengths include its strategic location within the university campus, availability of modern dental equipment, and a highly competent healthcare workforce. However, weaknesses were found in limited promotional efforts and underdeveloped collaborations with health insurance providers. Opportunities identified include potential expansion to 24-hour service and increased use of social media for promotion. Major threats involve rising competition from surrounding private dental hospitals and clinics. Conclusion: To improve its competitiveness, RSGM UNAND must strengthen its promotional strategies, build strategic partnerships with health insurance networks, and invest in digital technologies that support service expansion and public engagement.